Pendekatan Analisis Data Menggunakan NVivo-software untuk Penelitian Desain Logo Museum Nasional Jakarta - Sidik, Amelia; Mulya, Bodhiya Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2011)
Qualitative data analysis can be an exhausting, tough, and time-consuming work because the data obtained is so numerous, varied, and unstructured. However, this problem has been resolved by using computer-assisted qualitative data analysis software (CAQDAS). CAQDAS can help researchers to save, organize, explore data easily, and reduce the risk of damaging the raw data. In this article, the writer will explain about how to apply a quite popular CAQDAS application, NVivo, in the research of logo design of Museum Nasional Jakarta.